2017
DOI: 10.1002/hbm.23576
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal obesity and white matter microstructure in midlife

Abstract: The aging US population and the recent rise in the prevalence of obesity are two phenomena of great importance to public health. In addition, research suggests that midlife body mass index (BMI) is a risk factor for dementia, a particularly costly disease, in later life. BMI could influence brain health by adversely impacting cerebral white matter. Recently, greater BMI has been associated with lower white matter fractional anisotropy (FA), an index of tissue microstructure, as measured by diffusion-tensor ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 46 publications
2
58
2
Order By: Relevance
“…This observation may explain discrepant findings in the literature, as some studies reported beneficial effects of larger BMI or waist circumference on white matter microstructure (Birdsill et al, 2017), whilst other studies reported adverse effects Kullmann et al, 2015;Ronan et al, 2016). Previously we reported significant correlations between BMI and fornix white matter microstructure in a smaller group of older adults (Metzler-Baddeley et al, 2013), a result that was not replicated here.…”
Section: Discussioncontrasting
confidence: 91%
“…This observation may explain discrepant findings in the literature, as some studies reported beneficial effects of larger BMI or waist circumference on white matter microstructure (Birdsill et al, 2017), whilst other studies reported adverse effects Kullmann et al, 2015;Ronan et al, 2016). Previously we reported significant correlations between BMI and fornix white matter microstructure in a smaller group of older adults (Metzler-Baddeley et al, 2013), a result that was not replicated here.…”
Section: Discussioncontrasting
confidence: 91%
“…The observed positive relationship between FA in the UF and BMI was surprising, considering that previous studies generally find negative associations between white matter structural integrity and measures of obesity. However, indicators of increased weight have previously associated with increased white matter integrity or volume in several regions (Birdsill et al, 2017;Yokum et al, 2012). Moreover, higher FA in the UF has been found to correlate with sensitivity to punishment and reward-related activity in the nucleus accumbens (Camara, Rodriguez-Fornells, & Munte, 2010), further implicating changes in this tract with higher BMI as representative of differences in emotion and reward processing.…”
Section: Body Mass Index and Frontolimbic Structural Changesmentioning
confidence: 99%
“…Obesity and TBSS studies have generally described inverse associations between waist circumference (WC) or BMI and FA in tracts involved in reward-seeking (e.g., inferior fronto-occipital fasciculi, corpus callosum, and corticospinal tract) and cognitive control (e.g., inferior and superior longitudinal fasciculi) 23 25 . Although contradictory findings do exist 26 , most indicate that the higher the BMI or the WC, the lower the FA 27 31 . In addition, studies on physiological markers of stress have found reductions in global and regional FA values 32 34 linked to higher cortisol levels.…”
Section: Introductionmentioning
confidence: 98%